2008
DOI: 10.4103/0970-0218.39243
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of attendees in voluntary counseling and testing centers of a medical college hospital in coastal Karnataka

Abstract: Research Question:What are the socio-demographic profile and risk behavior pattern of seropositive attendees in the voluntary counseling and testing center (VCTC)?Study Design:Retrospective study.Setting:VCTC in the outpatient complex of Kasturba Medical College Hospital, Mangalore, Karnataka.Subjects:Records pertaining to all the 539 and 330 seropositive attendees during the years 2005 and 2006, respectively, were included in the study besides data from 2001 onwards in order to assess the time trend of human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 4 publications
4
13
0
Order By: Relevance
“…These findings are similar to the study conducted by Jayaram S et al 6 and to that of the study conducted by Safren SA et al (17%) 7 though the number of subjects with primary education was lesser than those with secondary education and above. In our study, 43.3% of the subjects were from outside Dakshina Kannada District.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are similar to the study conducted by Jayaram S et al 6 and to that of the study conducted by Safren SA et al (17%) 7 though the number of subjects with primary education was lesser than those with secondary education and above. In our study, 43.3% of the subjects were from outside Dakshina Kannada District.…”
Section: Discussionsupporting
confidence: 93%
“…The distribution according to educational status showed that the seropositivity was higher among the subjects with lesser education. These findings are similar to the study conducted by Jayaram et al 8 in Karnataka, India. Low education status and less awareness regarding safe sex can be the reason for high prevalence among this group of people.…”
Section: Discussionsupporting
confidence: 82%
“…4 High number of married persons having HIV/AIDS was also reported by Jayrama et al (70.3%). 8 This clearly indicates that most of the females get infection from their husbands. These labourers usually stay away from their families for long duration, get involved in promiscuous behaviour and get infected with HIV.…”
Section: Discussionmentioning
confidence: 99%